2021
DOI: 10.3390/jcs5030064
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Pressure-Induced-Flow Processing on the Morphology, Thermal and Mechanical Properties of Polypropylene Blends

Abstract: The pressure-induced-flow (PIF) processing can effectively prepare high-performance polymer materials. This paper studies the influence of pressure-induced-flow processing on the morphology, thermodynamic and mechanical properties of polypropylene (PP)/polyamide 6 (PA6) blends, PP/polyolefin elastomer (POE) blends and PP/thermoplastic urethane (TPU) blends. The results show that pressure-induced-flow processing can significantly improve the thermodynamic and mechanical properties of the blends by regulating in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Li et al 9 investigated the toughening efficiency of POE6202 on PP/POE blends, and showed that the impact strength of blends increased and then declined upon increasing of POE dosage, and the best performance was achieved when 20 wt% POE6202 was added. The toughening effect is also closely associated with the processing conditions 17–19 . Munoz‐Pascual's group 18 revealed that a higher mold temperature increased the impact resistance of PP/POE blends due to the lower shear and slower crystallization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al 9 investigated the toughening efficiency of POE6202 on PP/POE blends, and showed that the impact strength of blends increased and then declined upon increasing of POE dosage, and the best performance was achieved when 20 wt% POE6202 was added. The toughening effect is also closely associated with the processing conditions 17–19 . Munoz‐Pascual's group 18 revealed that a higher mold temperature increased the impact resistance of PP/POE blends due to the lower shear and slower crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…The toughening effect is also closely associated with the processing conditions. [17][18][19] Munoz-Pascual's group 18 revealed that a higher mold temperature increased the impact resistance of PP/POE blends due to the lower shear and slower crystallization.…”
mentioning
confidence: 99%
“…Therefore, a compatibilizer and surfactant are required to improve the dispersion and compatibility between the glass fibers, clay particles, and polymer in fiber-reinforced polymer composites. In particular, many earlier studies have utilized polypropylene-graft-maleic anhydride (PP-g-MA) [30][31][32] and polystyrene-block-poly(ethylene-ran-butylene)-block-polystyrene-graft maleic anhydride (SEBS-g-MA) [30,33] as the compatibilizer and toughening agent, respectively, and a cationic surfactant, viz., octadecyl-trimethyl-ammonium bromide (ODAB) for the dispersion and exfoliation of the nanoclay particles [34,35]. PP-g-MA has better ductility than PA6, and it can blend homogeneously with the PA6 resin through melt compounding at temperatures exceeding 200 • C. The resulting composite demonstrates improved crystallinity and tribological properties because maleated PP acts as a nucleating agent, stabilizes the crystalline site, and accelerates the nucleation of the polymer [36][37][38], but also reduces the interfacial tension between the PA6 chains, facilitating the uniform clay intercalation to polymer chains [27,39].…”
Section: Introductionmentioning
confidence: 99%